The Effect of Disclosure of Sustainability Reports, Leverage, and Company Size on Financial Performance in the Banking - Monica Diah Paramita; Januar Eko Prasetio (International Journal of Applied Business and International Management, 2025)
This study aims to empirically examine the effect of sustainability report disclosure, leverage, and company size on company financial performance (ROA). The sample consists of banking sector companies listed on the Indonesia Stock Exchange during the period 2021-2023. Data was collected through annual reports and sustainability reports using 78 samples from 26 companies using purposive sampling method, then analyzed using multiple linear regression. The results showed that sustainability report disclosure, company size, and leverage have a significant relationship with financial performance. Keywords: Sustainability Report, Leverage, Company Size, Financial Performance (ROA).